Innovations in crisis management at the regional level - S. S. Shirokov; T. V. Kakatunova; V. G. Halin (Путеводитель предпринимателя, 2020)
The role of innovation in the crisis management organizations is proved. Measures to support innovation in the organizations that are in a crisis situation are given. Regional innovation infrastructure, focused on the implementation of innovation in organizations, which are in crisis, is considered.